Tpo1‐mediated spermine and spermidine export controls cell cycle delay and times antioxidant protein expression during the oxidative stress response. (18th October 2013) - Krüger, Antje; Vowinckel, Jakob; Mülleder, Michael; Grote, Phillip; Capuano, Floriana; Bluemlein, Katharina; Ralser, Markus
Abstract : Cells counteract oxidative stress by altering metabolism, cell cycle and gene expression. However, the mechanisms that coordinate these adaptations are only marginally understood. Here we provide evidence that timing of these responses in yeast requires export of the polyamines spermidine and spermine. We show that during hydrogen peroxide (H2 O2 ) exposure, the polyamine transporter Tpo1 controls spermidine and spermine concentrations and mediates induction of antioxidant proteins, including Hsp70, Hsp90, Hsp104 and Sod1. Moreover, Tpo1 determines a cell cycle delay during adaptation to increased oxidant levels, and affects H2 O2 tolerance. Thus, central components of the stress response are timed through Tpo1‐controlled polyamine export. Abstract : Cellular export of the metabolites spermine and spermidine is induced under oxidative stress to control the timing of antioxidant gene expression and cell cycle delay and to promote cell survival.